Етико-лінгвістичні особливості ділового телефонного спілкування англійською мовою - Коротка, Наталія Володимирівна (My University, 2019)
Стаття присвячена дослідженню специфіки ділового спілкування. Особлива увага приділяється етико-лінгвістичним розвідкам у галузі ділового телефонного спілкування. У статті узагальнюється поняття мовного етикету, наводяться його правила; та особливості сучасної ділової етики, наводяться рекомендації щодо ділової телефонної розмови англійською мовою. У статті розглядаються стійкі етикетні вирази, адже дотримуючись правил етикету телефонної розмови, можна демонструвати не тільки свій діловий професіоналізм, а й загальну культуру, освіченість; формули вираження власної думки; моделі ділової телефонної комунікації; також наведені приклади кліше, необхідні для здійснення даного виду спілкування англійською мовою, відповідно до етичних норм ділової телефонної розмови. Стаття робить акцент на майстерності ведення переговорів, яка вимагає не лише індивідуальних якостей, але й етико-лінгвістичної та психо-лінгвістичної підготовки, для того, щоб домогтися максимальної результативності від процесу комунікації. The article is devoted to the study of the specifics of business communication. Particular attention is paid to ethical and linguistic research in the field of business telephone communication. The article summarizes the concept of language etiquette, provides its rules; discusses the features of modern business ethics, specifies the role of vertical (status) and horizontal (social) distance, provides recommendations for business English telephone conversation. The article deals with stable etiquette expressions, because observing the rules of etiquette of telephone conversation, you can demonstrate not only your business professionalism, but also the general culture, education; formula of expression of your own opinion; models of business telephone communication; the article also provides examples of clichés necessary for the implementation of this type of English communication, according to the ethical standards of business telephone conversation; the author considers the use of a conditional mood for expressing a polite attitude to the respondent, tactics of avoiding straight refusal, which are common depending on a particular English-speaking country. The article focuses on the skill of negotiation, which requires not only individual qualities, but also ethical and linguistic, psychological and linguistic training, in order to achieve maximum effectiveness of the communication process.
Keywords: моделі ділової телефонної комунікації; етичні норми ділової телефонної розмови; мовні кліше; монологічні та діалогічні форми ділової телефонної комунікації; the models of business telephone communication; ethical standards of business telephone conversation; speech clichés; monological and dialogical forms of business telephone communication; кафедра ділової іноземної мови та міжнародної комунікації